The Role of Strategic Analysis (Strength, Weakness, Opportunity, Threats) SWOT in Improvement of Performance at Benghazi Medical Center - Randa Gadalla; Douaa Alzidani; Abdulrahim Alkhashmi; Fatima Alzahra Alfarsi; Abdulrahman Alwerfali; Mohammed Almnfi (AlQalam Journal of Medical and Applied Sciences, 2024)
This study conducted to measure the role of strengths, weaknesses, opportunities, threats Analysis "SWOT Analysis" in improving the performance at Benghazi Medical Centre. A descriptive cross-sectional study was conducted among patients staying in the medical department in a BMC. Data collected it was revised, coded and fed to statistical software SPSS "Version 23". The study was based on a questionnaire that was distributed to 300 Libyan patients’ participants in BMC (Department of Internal Medicine). The current study illustrated that 4.12 of the sample size agree with (the center’s facilities are easily accessible,) and 3.93 of them agree with (lack of medication in the center’s pharmacy staff.), while 3.57 of them didn’t agree with (there are training opportunities for students and recent graduates.), and about 3.29 of the sample size neutral with (shortage of nursing staff.). The study suggests that the necessity of strengthening hospital management in providing the service correctly and for the first time. The necessity of providing a sufficient number of qualified nurses. أجريت هذه الدراسة لقياس دور تحليل نقاط القوة والضعف والفرص والتهديدات في تحسين الأداء بمركز بنغازي الطبي, تم إجراء دراسة وصفية مقطعية بين المرضى المقيمين في قسم الطب في مركز بنغازي الطبي وتمت مراجعة البيانات التي تم الإصدار 23 . اعتمدت الدراسة على استبيان تم توزيعه على 300 SPSSجمعها وترميزها وتغذيتها بالبرنامج الإحصائي مريض ليبي مشارك في مركز بنغازي الطبي (قسم الطب الباطني ). وكشفت الدراسة الحالية أن قوة مركز بنغازي الطبي البالغة 4.12% لديها أعلى متوسط درجات حيث يمكن الوصول إلى مرافق المركز بسهولة,و نسبة 2.66 نقاط الضعف في مركز بنغازي الطبي كان نقص الادوية لدي موظفي الصيديلية في مركز بنغازي الطبي.وكان أعلى متوسط 2.37% هناك فرص تدريب للطلاب والخريجين الجدد.وكان 3.29% اعلي متوسط للتهديدات وتتمثل في النظافة والغذاء. وتشير الدراسة إلى ضرورة تعزيز إدارة المستشفى في تقديم الخدمة بشكل صحيح ولأول مرة ضرورة توفير العدد الكافي من الممرضين المؤهلين.